An Expeditious One‐Pot Two‐Component Synthesis of Quinoxaline Derivatives in Natural Deep Eutectic Solvents (NADESs). Issue 11 (14th March 2023) - Das, Arindam; Dey, Sovan; Naresh Yadav, Ram; Jyoti Boruah, Palash; Bakli, Prerana; Sarkar, Sourav; Mahata, Partha; Kumar Paul, Amit; Hossain, Firoj
Abstract: A facile and eco‐friendly sustainable synthesis of functionalized quinoxaline derivatives from 1, 2‐diaminobenzenes and 2‐bromoacetophenones via a one‐pot two‐component reaction using choline chloride (ChCl): glycerol as a bio‐renewable DES has been developed. In this protocol, nucleophilic 1, 2‐diaminobenzenes are mixed with phenacyl bromides or 3‐(bromoacetyl) coumarin to produce quinoxaline derivatives in a high yield (up to 96 %), with a clean reaction profile without the use of a solvent or catalyst at ambient temperature (80 °C). The presence of DES is proven to be essential for assuring efficient transformation, as the product yield was extremely low with a slow reaction profile in the absence of this media. The DES media could be recycled and reused up to five times without losing its efficiency or affecting the chemical yield of the reaction. In the showcase study, the reaction was also scaled up to the gram scale (10 mmol scale), revealing the synthetic potential of the current approach. A DFT calculation has been also performed to probe the mechanism and reversal of the regioselectivity in the products formation. Abstract : A facile and eco‐friendly sustainable synthesis of functionalized quinoxaline derivatives from 1, 2‐diaminobenzenes and 2‐bromoacetophenones via a one‐pot two‐component reaction using choline chloride (ChCl): glycerol as a bio‐renewable DES has been developed. A DFT calculation was also studied to support the experimental result and to determine the course of the reaction to gain a deeper understanding of the unusual regioselectivity.